THE RELATIONSHIP OF AFFECTIVE AND COGNITIVE RESPONSES AND THEIR EFFECT ON TYPICAL PERSON ENDORSER BRAND IMAGE COSMETICS - Rama Dwissa Wiana; Dwika Lutfhi Permana; Janeru Kennedy (International Journal of Economy, Education and Entrepreneurship, 2021)
The population of this study were people who knew and had heard of or seen Cosmetics ads. Because the population is not limited in number, a study sample of 100 respondents was taken, consisting of 50 male respondents and 50 female respondents. Sampling technique with accidental sampling. Data is collected with a questionnaire. The data analysis techniques used are multiple linear regression tests and simple linear regression tests. The results showed: partially affective  response to the typical person endorser in testimonial ads on brand image has a positive effect on the brand image of Cosmetics, but the more dominant influence is male respondents, partial cognitive response to typical person endorsers in testimonial ads on brand image positively affects brand image Cosmetics , but the more dominant influence is female respondents, Together affective  responses to typical person endorsers in testimonial advertisements on brand images and cognitive responses to typical person endorsers in testimonial advertisements on brand images have a positive effect on brand image Cosmetics, among these 2 variables the greatest influence is the variable affective response to the typical person endorser in testimonial ads on brand image  male respondents, brand image positively affects the brand attitude of Cosmetics